2017
DOI: 10.1016/j.aogh.2016.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Outpatients After the 3.11 Complex Disaster in Fukushima, Japan

Abstract: There were time- and disease-dependent changes in the numbers of psychiatric care-seeking individuals after the 3.11 complex disaster in Fukushima.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Second, it may be related to the cultural and social factors. Unlike surveys after disasters all over the world, Hori et al reported that in 2011 after 3.11 new outpatients of the depressive episode or other mood disorders in Fukushima Prefecture had decreased visits and estimated the cultural background [ 17 ]. They speculated that altruistic feelings of unity and nationalistic eagerness for recovery prevailed in Japan after disaster, and many residents in disaster-stricken areas may have had a heightened sense of purpose to overcome the threat of radiation exposure and to rebuild their hometowns [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, it may be related to the cultural and social factors. Unlike surveys after disasters all over the world, Hori et al reported that in 2011 after 3.11 new outpatients of the depressive episode or other mood disorders in Fukushima Prefecture had decreased visits and estimated the cultural background [ 17 ]. They speculated that altruistic feelings of unity and nationalistic eagerness for recovery prevailed in Japan after disaster, and many residents in disaster-stricken areas may have had a heightened sense of purpose to overcome the threat of radiation exposure and to rebuild their hometowns [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…21 For non-FHMS studies (n = 46; 60.5%), a large number of the studies used convenience samples and focused on evacuees (living in and out of the Fukushima prefecture), children, and older adults. Other study populations focused on specific populations, such as hospital patients, 15,23,45,47,54,85,86 caregivers, 19,71 students, 16,30,33,42,[48][49][50]62 and workers of various occupations. Specifically, a series of studies were conducted among the NPP workers.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Post-traumatic stress disorder (PTSD) and depression significantly impair the social functioning of those affected and are often recognised as the most visible mental health effects on survivors, as was the case with the Great East Japan Earthquake (GEJE) of 2011. [1][2][3][4] In the present study, however, we would like to focus on manic and hypomanic episodes that occurred in the victims of the GEJE. 5 6 While bipolar disorder requires medical treatment, social functioning of the patient tends to be maintained during the hypomanic episode.…”
Section: Introductionmentioning
confidence: 99%